2011
DOI: 10.1007/s11469-011-9340-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-Compassion Mitigate the Association Between Childhood Maltreatment and Later Emotion Regulation Difficulties? A Preliminary Investigation

Abstract: Child maltreatment-related outcomes range from no symptom expression to suicide. Increasingly, the diverse presentations have been conceptualized as core system dysregulation, including emotion dysregulation. Self-compassion has been advanced as a self-regulation strategy for countering negative self-directed emotions. This study explored whether individual differences in self-compassion would play a role in loosening the associations among childhood maltreatment severity and later emotion regulation difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
122
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 47 publications
14
122
1
Order By: Relevance
“…Tanaka et al (2011) found that higher levels of childhood emotional abuse, emotional neglect and physical abuse were associated with lower levels of SC; and that adolescents with lower SC levels were more likely to suffer from psychological distress leading to problems with substance abuse and in some instances attempted suicide among a sample of at-risk youth receiving child protective services. Relatedly, Vettese et al (2011) found that SC concurrently mediated the association between childhood maltreatment and later adolescent emotional dysregulation in a sample of youth seeking treatment for substance abuse above and beyond other risk factors including childhood maltreatment history, current psychological distress and addiction severity.…”
Section: Cross-sectional Studymentioning
confidence: 92%
“…Tanaka et al (2011) found that higher levels of childhood emotional abuse, emotional neglect and physical abuse were associated with lower levels of SC; and that adolescents with lower SC levels were more likely to suffer from psychological distress leading to problems with substance abuse and in some instances attempted suicide among a sample of at-risk youth receiving child protective services. Relatedly, Vettese et al (2011) found that SC concurrently mediated the association between childhood maltreatment and later adolescent emotional dysregulation in a sample of youth seeking treatment for substance abuse above and beyond other risk factors including childhood maltreatment history, current psychological distress and addiction severity.…”
Section: Cross-sectional Studymentioning
confidence: 92%
“…Others have proposed that the disturbance of the development of affect regulation and adaptive functioning (Kim & Cicchetti, 2010), including associated self-regulating strategies such as self-compassion (Vettese, Dyer, Li, & Wekerle, 2011) is implicated in the relationship between abuse and depression. Affect 4 regulation is defined here as the ability to modulate one's emotional states without undue attempts to avoid or suppress difficult emotions.…”
Section: Abuse Affect Regulation and Depressionmentioning
confidence: 99%
“…Overall, these findings point out that self-compassion is associated with positive psychological indicators (e.g., early memories of warmth and Running head: Self-compassion in adolescence 3 safeness, secure attachment, mindfulness, mental health, life satisfaction, emotional well-being; Cunha, Martinho, Xavier, & Espírito-Santo, 2013;Bluth & Blanton, 2014;Marshall, Parker, Ciarrochi, Sahdra, Jackson, & Heaven, 2015;Neff & McGehee, 2010). Inversely association patterns between self-compassion and maladaptive outcomes were found (e.g., negative affect, aggression, trauma-related symptoms, depression, anxiety; Barry, Loflin, & Douvette, 2015;Bluth & Blanton, 2015;Tanaka, Wekerle, Shmuck, & Paglia-Boak, 2011;Vettese, Dyer, Li, & Wekerle, 2011;Zeller, Yuval, Nitzan-Assayag, & Bernstein, 2014).…”
Section: Introductionmentioning
confidence: 99%